Hamas and ideology : Sheikh Yusuf al-Qaradawi on the Jews, Zionism and Israel /: Sheikh Yusuf al-Qaradawi on the Jews, Zionism and Israel. (2017) - Bartal, Shaul; Rubinsten-Shemer, Nesya
No abstract available